Novel Simplified and Rapid Method for Screening and Isolation of Polyunsaturated Fatty Acids Producing Marine Bacteria. (15th August 2012) - Tilay, Ashwini; Annapure, Uday
Abstract : Bacterial production of polyunsaturated fatty acids (PUFAs) is a potential biotechnological approach for production of valuable nutraceuticals. Reliable method for screening of number of strains within short period of time is great need. Here, we report a novel simplified method for screening and isolation of PUFA-producing bacteria by direct visualization using the H2 O2 -plate assay. The oxidative stability of PUFAs in growing bacteria towards added H2 O2 is a distinguishing characteristic between the PUFAs producers (no zone of inhibition) and non-PUFAs producers (zone of inhibition) by direct visualization. The confirmation of assay results was performed by injecting fatty acid methyl esters (FAMEs) produced by selected marine bacteria to Gas Chromatography-Mass Spectrometry (GCMS). To date, this assay is the most effective, inexpensive, and specific method for bacteria producing PUFAs and shows drastically reduction in the number of samples thus saves the time, effort, and cost of screening and isolating strains of bacterial PUFAs producers.